The Main Peculiarities of Development of Corporate Law in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
In this Article its author in a historical retrospection describes speci cs of legal regulation of those aspects which relate to theuse of corporate forms for legal entities to perform economic activities under Kazakhstani legislation of the soviet time. The attentionis paid to the phenomena of perception of concepts of the modern corporate law from legislation of foreign jurisdictions. Based onthe analysis carried out by the author with respect to foreign and Kazakstani scienti c and legal sources the author proposes his viewconcerning content of such legal concepts as corporate relations and a corporation. There are main legislative acts of corporatelaw in Kazakhstan, as well as its most noticeable features pointed out in this Article. The authors view regarding tendencies of furtherdevelopment of the corporate legislation in Kazakhstan, as well as directions of its reformation (modernization) is also offered.